(untitled) (International Journal of Engineering and Computer Science, 2015)
For almost all the colleges and universities, having such a large amount of information, with regard to accurately and efficiently carry out the student’s management on the basis of a full grasp of information, the extent of difficult task is incomprehensible. Through the SIMS, we can realize the management of students information network-based digitally, groove and gather the students information realtimely, precisely, minimize the workload of students information management, assist the scientific and effectiveness of students information management, thus to uphold the management of college students to carry out high efficiently. The common way to represent a relational database is a tabular structure, where each table represents a relation. The extent of difficult task is unimaginable for each of the colleges and universities, having such a large amount of data, in order to accurately and efficiently carries out the student’s management on the basis of a full grasp of information. We now can realize the management of students information network-based digitally, groove and gather the students information real-timely, precisely, minimize the workload of students information management, stimulate the scientific and effectiveness of students information management through the SIMS, and hence we can uphold the management of college students to carry out high efficiently. The common way to represent a relational database is a tabular structure, where each table represents a relation.